Low serum levels of meteorin-like/subfatin is related to obesity and insulin resistance - Çavlı, Cundullah; Önalan, Erhan; Yakar, Burkay; Dönder, Emir; Kavuran, İlay Buran; Etem, Ebru (My University, 2022)
Introduction: Meteorin-like (Metrnl), also known as subfatin is a newly discovered adipokine of adipocyte origin that may play a role in obesity and insulin resistance. The current study aimed to investigate the association between subfatin and biochemical values, demographic characteristics, and insulin resistance in obese patients and healthy controls.Methods: This cross-sectional study included 59 obese patients with sex and age-matched group of 41 healthy controls. An enzyme-linked immunosorbent assay (ELISA) was used to measure the serum levels of Subfatin (Metrnl), and the correlations of Metrnl level with anthropometric parameters, HOMA index, and biochemical measurements were assessed.Results: The levels of BMI (p<0.001), insulin (p=0.002), and HOMA-IR score (p<0.001) were significantly higher in obese patients than controls. The serum levels of Subfatin were found to be lower in obese patients (1.85 [1.35–5.51] ng/ml) compared to the healthy controls (21.82 [12.61–27.76] ng/ml) (p<0.001). Subfatin had a significantly negative relationship with age (r =-0.250, p=0.012), weight (r =-0.373, p=0.001), BMI (r =-0.492, p=0.001), HbA1c (r =-0.209, p=0.037), LDL (r =-0.264, p=0.008), HOMA-IR (r =-0.223, p=0.026), and glucose (r =-0.376, p<0.001). There was a significantly positive correlation between subfatin and height (r=0.321, p=0.001).Conclusion: These results show that levels of subfatin were decreased in obese patients. There is a relationship between circulating amounts of subfatin hormone and age, weight, height, LDL-cholesterol, glucose, hbA1c, and HOMA-IR. Subfatin might be a new biomarker of obesity and insulin resistance.Keywords: Meteorin-like/subfatin, adiposity, insulin resistance, adipokines, biomarkers, diabetes mellitus type 2
Keywords: Insulin resistance; adipokines; biomarkers; meteroin-like/subfatin; adiposity; diabetes mellitus type 2